2013
DOI: 10.1089/ham.2013.1030
|View full text |Cite
|
Sign up to set email alerts
|

Is Poor Sleep Quality at High Altitude Separate from Acute Mountain Sickness? Factor Structure and Internal Consistency of the Lake Louise Score Questionnaire

Abstract: The sleep quality item of the LLSQ was weakly related to the other items of the LLSQ. Future research should further investigate whether impaired sleep at altitude should be considered separately from other symptoms of AMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 17 publications
3
21
0
Order By: Relevance
“…The observed 66% of overall sleep impairment was similar to prior high altitude sleep studies, where 32%-60% of subjects reported disturbed sleep ( Jafarian et al, 2008). Sleep disturbances at high altitude are frequent, and sleep quality has been shown to have the weakest correlation with other AMS symptoms (Macinnis et al, 2013). While sleep time was significantly decreased in the EPAP group, it was difficult to determine if this was due to the discomfort of increased work of breathing with expiratory resistance.…”
Section: Discussionsupporting
confidence: 79%
“…The observed 66% of overall sleep impairment was similar to prior high altitude sleep studies, where 32%-60% of subjects reported disturbed sleep ( Jafarian et al, 2008). Sleep disturbances at high altitude are frequent, and sleep quality has been shown to have the weakest correlation with other AMS symptoms (Macinnis et al, 2013). While sleep time was significantly decreased in the EPAP group, it was difficult to determine if this was due to the discomfort of increased work of breathing with expiratory resistance.…”
Section: Discussionsupporting
confidence: 79%
“…Recently this discussion has intensified. Two independent reports in 2013 provided empirical evidence that sleep disturbance is discordant from other symptoms of AMS (MacInnis et al, 2013;Hall et al, 2014). Hall et al (2014) used network analysis of data from 292 research volunteers exposed to altitudes from 3650 to 5200 m to demonstrate that sleep disturbance correlated poorly with other symptoms of AMS.…”
Section: Rationale For Revising the Lake Louise Ams Scorementioning
confidence: 99%
“…Importantly, sleep disturbance was absent in 40% of cases with severe headache, long considered a hallmark of AMS. MacInnis et al (2013) applied factor analysis to Lake Louise AMS scores of 491 Nepalese pilgrims at 4390 m and revealed that sleep had only a weak relationship with the other four symptoms in the score. Milledge also expressed doubt as to whether sleep disturbance was a symptom of AMS, or rather an effect of hypoxia per se, based on his own experience with AMS studies (Milledge, 2014).…”
Section: Rationale For Revising the Lake Louise Ams Scorementioning
confidence: 99%
See 1 more Smart Citation
“…In the recent prospective study (MacInnis et al, 2013a), forty-eight pairs of siblings were identified, but family history was not found to be a risk factor for AMS although signs of familial aggregation were evident. The pilgrims have also helped out with trying to refine the Lake Louise Score Questionnaire and AMS diagnosis (Macinnis et al, 2012;2013b). Finally, oxygen saturation and diastolic blood pressure in 41 pilgrims were negatively and positively correlated with Lake Louise Score, respectively.…”
Section: Overview On Pilgrimagesmentioning
confidence: 99%